The at-wavelength metrology facility for UV- and XUV-reflection and diffraction optics at BESSY-II - Schäfers, F. (J Synchrotron Radiat, 2016)
A technology center for the production of high-precision reflection gratings has been established. Within this project a new optics beamline and a versatile reflectometer for at-wavelength characterization of UV- and XUV-reflection gratings and other (nano-) optical elements has been set up at BESSY-II. The Plane Grating Monochromator beamline operated in collimated light (c-PGM) is equipped with an SX700 monochromator, of which the blazed gratings (600 and 1200 lines mm(−1)) have been recently exchanged for new ones of improved performance produced in-house. Over the operating range from 10 to 2000 eV this beamline has very high spectral purity achieved by (i) a four-mirror arrangement of different coatings which can be inserted into the beam at different angles and (ii) by absorber filters for high-order suppression. Stray light and scattered radiation is removed efficiently by double sets of in situ exchangeable apertures and slits. By use of in- and off-plane bending-magnet radiation the beamline can be adjusted to either linear or elliptical polarization. One of the main features of a novel 11-axes reflectometer is the possibility to incorporate real life-sized gratings. The samples are adjustable within six degrees of freedom by a newly developed UHV-tripod system carrying a load up to 4 kg, and the reflectivity can be measured between 0 and 90° incidence angle for both s- and p-polarization geometry. This novel powerful metrology facility has gone into operation recently and is now open for external users. First results on optical performance and measurements on multilayer gratings will be presented here.